Development of Affinity Adsorbent System for Purification of Protease - Abdul Haris Watoni; Sapto Raharjo; Husein H. Bahti; Soetijoso Soemitro (Jurnal Matematika & Sains, 2002)
The development of affinity adsorbent system for purification of protease produced by Bacillus sp. BAC-4 has been investigated. The research is initiated from preparation of non porous silica, aminopropyl silica matrix, and affinity adsorbent. In this research, the approximately spherical form of non porous silica with diameter of 1 â 15 Î¼m and aminopropyl silica matrix has been synthesized. This matrices contains 65,7 Î¼mol/g of amino group and show the similar FTIR spectrum to that of standard aminopropyl silica. Preparation result of affinity adsorbent shows that 10% n-butanol is the most applicable affinity ligand with 99,96% binding capacity to the matrix. The optimum activity of the purified protease with affinity adsorbent system is in the 0.05 N Tris HCl buffer pH 8.0 at 550C for 15 minutes with the degree of purity of 1248âfold to that in the crude extract.